2005
DOI: 10.1002/jmri.20438
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility effects on the accuracy of MR temperature monitoring by the proton resonance frequency method

Abstract: Purpose:To evaluate the error of MR temperature assessment based on the temperature-dependent Larmor frequency shift of water protons, which can result from susceptibility effects caused by the radiofrequency (RF) applicator. Materials and Methods:Local frequency shifts due to RF applicator displacements were simulated numerically by means of a three-dimensional elementary dipole model. Experimental examinations using a water tank phantom equipped with a high-precision screw thread were applied to examine temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
(14 reference statements)
0
22
0
Order By: Relevance
“…A decreased SNR due to incomplete filtering and to possible residual organ displacements may occur and thereby increase the standard deviation of temperature estimation [21]. Therefore, additional image processing was performed off-line as follows [22]: first, in each pixel of a ROI located outside the heated region, the standard deviation of the MR temperature measurements was calculated before, during and after RF ablation; second, residual motion was corrected using an atlas of reference data (magnitude and corresponding phase images) for the different liver positions recorded before the heating phase; third, if the temperature standard deviation (outside the RF ablation zone) following the above-mentioned correction exceeded 10% of a predefined maximal value, the temperature image was removed from the TD calculation process.…”
Section: Post Processingmentioning
confidence: 99%
“…A decreased SNR due to incomplete filtering and to possible residual organ displacements may occur and thereby increase the standard deviation of temperature estimation [21]. Therefore, additional image processing was performed off-line as follows [22]: first, in each pixel of a ROI located outside the heated region, the standard deviation of the MR temperature measurements was calculated before, during and after RF ablation; second, residual motion was corrected using an atlas of reference data (magnitude and corresponding phase images) for the different liver positions recorded before the heating phase; third, if the temperature standard deviation (outside the RF ablation zone) following the above-mentioned correction exceeded 10% of a predefined maximal value, the temperature image was removed from the TD calculation process.…”
Section: Post Processingmentioning
confidence: 99%
“…Evaluation of temperature mapping has been mainly focused on the analysis of accuracy and precision (18,20,30). A high precision of temperature values was published for both EPI and GRE sequences (18).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies reported that any temperature above 52°C caused irreversible tissue damage (24,25). Sixty degrees C was chosen in order to compensate for eventual breathing-induced temperature misregistrations reported especially for the liver dome (26) and for errors induced by the use of metallic applicators (20). We used a binary classification test to evaluate the validity of the temperature maps (see Fig.…”
Section: Segmentation Of the Coagulation Zonementioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the temperature measurements using MR thermometry is comparable to that of the invasive methods (20). However, conventional MR thermometry methods, such as PRFS, are sensitive to local magnetic susceptibility associated with tissue anatomy and interventional medical devices (21)(22)(23), large fat contents within the region of interest (ROI) (14), motion artifacts (5), and magnetic field drift (20). Alternative MR thermometry techniques have been developed over the last twenty years to exploit MR properties that afford high temperature sensitivity and measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%